Indeks Massa Tubuh Pra-Hamil sebagai Faktor Risiko Terjadinya Bayi Berat Lahir Rendah - Zulia Yasminanindita Fahmi (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2020)
Backgrounds: Infant with low birth weight (2500 gram) become a major factor that influence neonatal death, postneonatal death, and morbidity in both developed and developing countries. One thing that influence the quality of infant’s life since day one until two years old is mother’s nutritional status. Mother’s nutritional status shows the quality and quantity of nutritional intake fulfillment and determine it by measuring pre-pregnancy body mass index. Methods: using literature review by summarizing and comparing the result presented in the article. Result: mothers both normal and abnormal body mass index risk deliver infant with low birth weight. Conclusion: pre-pregnancy body mass index as rsik factor for the incidence of infant with low birth weight.